Development of Dispersive Liquid-Liquid Microextraction Procedure for Trace Determination of Malathion Pesticide in Urine Samples - Maryam RAMIN; Monireh KHADEM; Fariborz OMIDI; Mehran POURHOSEIN; Farideh GOLBABAEI; Seyed Jamaleddin SHAHTAHERI (Tehran University of Medical Sciences, 2019)
Background: Measurement of pesticides in biological matrices is become a serious challenge for researches because of their very low concentration in different matrices. The aim of this study was to develop a new sam-ple preparation method with high accuracy and validity, simplicity and short retention time for determination of malathion. Methods: Dispersive liquid-liquid micro-extraction (DLLME) technique coupled with high-performance liq-uid chromatography equipped with ultraviolet detector (HPLC-UV) developed for trace extraction and deter-mination of malathion pesticide in human urine samples. This study was done in 2017 at Tehran University of Medical Sciences, Tehran, Iran. One variable at a time (OVAT) method was used to optimize parameters af-fecting the malathion extraction. Different parameters such as extraction solvent, disperser solvent, and vol-ume of the extraction solvent, volume of the disperser solvent, centrifugation time and speed, salt addition, and sample pH were studied and optimized. Results: Under the optimized conditions, the limit of detection and enrichment factor of the method were 0.5 μg L-1 and 200, respectively. The calibration curve was linear in the concentration range of 2-250 μg L-1. The relative standard deviation for six replicate experiments at 200 μg L-1 concentration was less than 3%. The rela-tive recoveries of spiked urine samples were 96.3%, 101.7% and 97.3% at three different concentration levels of 50, 200 and 1000 μg L-1, respectively. Conclusion: DLLME procedure was successfully developed for the extraction of malathion from human urine samples. Compared to other extraction techniques, the proposed procedure had some advantages such as shorter extraction time, better reproducibility, and higher enrichment factor.